2019
DOI: 10.1002/ptr.6269
|View full text |Cite|
|
Sign up to set email alerts
|

SIRT1/AMPK and Akt/eNOS signaling pathways are involved in endothelial protection of total aralosides of Aralia elata (Miq) Seem against high‐fat diet‐induced atherosclerosis in ApoE−/− mice

Abstract: Total aralosides of Aralia elata (Miq) Seem (TASAESs) possess multiple pharmacological activity, such as anti‐inflammation, antioxidation, and antiapoptosis. However, there is no literature reporting the antiatherosclerotic effect and mechanism of TASAES so far. The aim of this study was to investigate the antiatherosclerotic effects in high‐fat diet‐induced ApoE−/− mice and potential mechanism of TASAES in ox‐LDL‐injured endothelial cells. In vivo assay, our data demonstrated that TASAES significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Recently, many natural products have been studied to determine their impact on atherosclerosis [18]. Our group and several others have reported that TASAES exerts therapeutic effects on myocardial damage [34,35] and atherosclerosis [22,23]. AsC, isolated from TASAES, was also reported to have powerful cardioprotective effects against ischemia-reperfusion injury in our previous study [20,21].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Recently, many natural products have been studied to determine their impact on atherosclerosis [18]. Our group and several others have reported that TASAES exerts therapeutic effects on myocardial damage [34,35] and atherosclerosis [22,23]. AsC, isolated from TASAES, was also reported to have powerful cardioprotective effects against ischemia-reperfusion injury in our previous study [20,21].…”
Section: Discussionmentioning
confidence: 84%
“…After rinsing, the sections were incubated for 1 h with the secondary antibody at room temperature and then incubated with 0.5 g/L DAPI containing antifluorescence quenching agent for 5 min. Images were obtained with a the Tissue FAXS microscope (Tissue FAX plus; Tissue Gnostics, Vienna, Austria) and analyzed based on our previous method [22].…”
Section: Histological and Immunohistochemical Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-established that dyslipidemia is a crucial risk factor for atherosclerosis and regulation of blood lipid profiles has been given priority in the treatment of atherosclerotic CVDs (2,5). Moreover, therapeutic approaches protecting against vascular intimal impairment have been proved to inhibit atheroma lesion progression (6,7). Currently, several modern drugs such as statins have been used for the treatment of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that triterpenoid saponins from AS leaves exert antitumor effects [18], and the bark and roots of AS have been used as tonics and diuretics in the treatment of the common cold, gastric ulcer, diabetes, neurasthenia, hepatitis, and inflammatory diseases in Chinese folk medicine [19]. Furthermore, AS exhibits a series of pharmacological functions, including anti-inflammatory, antioxidant, hypolipidemic, and antidiabetic properties [20,21]. Despite the development and application of AS, few studies have focused on it in preventing EC senescence.…”
Section: Introductionmentioning
confidence: 99%